Peningkatan Kemampuan Menulis Teks Biografi Melalui Penggunaan Media Infografis Pada Siswa Kelas X-10 SMA Negeri 2 Semarang - Rikha Apriliyana, Anjelia; Asropah; Agus Wismanto; Umi Chasanah (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the biographical writing skills of Grade X-10 students at SMA Negeri 2 Semarang through the use of infographic media. The background of the study stems from the students’ low interest and ability in composing biographical texts, as well as the frequent occurrence of written work that simply copies information from the internet without proper paraphrasing or in-depth understanding. This classroom action research was conducted in two cycles, involving the stages of planning, implementation, observation, and reflection. In the first cycle, students wrote biographical texts about their idols in paragraph form. In the second cycle, the texts were presented as infographics to enhance engagement and interest. The results indicated a significant improvement from the pre-cycle to the first cycle, and a more optimal improvement in the second cycle, during which all students exceeded the Minimum Mastery Criteria (KKM). The use of infographic media proved effective in increasing students’ motivation and creativity, while also making the learning process more interactive and enjoyable. Thus, integrating infographic media into biographical writing instruction can enhance the quality of students’ learning outcomes.